Banking and Finance Management System Human Resource Part Ii: (Learning Management, Training Management, Competency Management, Succession Planning, and Employee Self-Service): Vol.3, No.1B (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2024)
Banks, licensed to receive customer deposits and provide loans, offer various financial services such as currency exchange, wealth management, and safe deposit boxes. The banking and finance industry performs various functions, with commercial banks using payment networks and loan functions to deposit funds. In contrast, customers use checking accounts and debit cards to pay bills or make purchases. Human resource management (HRM) is critical in the service-oriented banking industry. Banks face two main challenges: managing people and managing risks. How these two challenges are handled determines a bank's success in the industry.